CONNECTING GLOBAL AND LOCAL INDONESIAN RELIGIOUS ENVIRONMENTAL MOVEMENTS - Jonathan D Smith (Universitas Gadjah Mada, 2017)
This article discusses connections between transnational multi-faith social movements addressing climate change on a global scale with local expressions of religion and ecology in Indonesia. It connects two trends in literature on religion and ecology: 1) spatial analysis of religion and the natural environment and 2) studies of religious environmental social movements. Many studies of these movements put religious activists at the center, which suggests that they operate in a separate zone, somewhat disconnected from the local communities they aim to represent and reform. This articles argues that religious environmental movements can be better understood by placing them in the middle, as actors embedded in and shaped by overlapping global and local spaces. The article begins with a brief review of literature on religion and ecology relevant to a spatial analysis of religion and environmental social movements. It then argues that studies about religious environmental movements can be enriched by studying how movements are embedded in global and local contexts. It provides examples of how the Indonesian context (among others) has helped to shape global religious environmental movements. Next, the article presents case studies in Indonesia demonstrating how environmental activists share a dynamic relationship with their contexts, and how religious environmental discourses are co-created by local communities and religious activists. The article concludes with suggestions for further study about creative adaption to climate change at the local and global level.